Intra-operative deep brain stimulation of the periaqueductal grey matter modulates blood pressure and heart rate variability in humans. - Green, A; Hyam, J; Williams, C; Wang, S; Shlugman, D; Stein, J; Paterson, D; Aziz, T (2010)
INTRODUCTION:   Deep brain stimulation applied to the periaqueductal grey matter (PAG) of the midbrain in humans has been shown to increase or decrease arterial blood pressure during rest and to resist the postural fall on standing. The mechanism by which this effect is elicited is unknown. We hypothesize that PAG stimulation modulates performance of the autonomic nervous system. METHODS:   Five consecutive male patients of a mean age of 49.1 years underwent PAG stimulation for intractable pain syndromes. Intra-operatively, blood pressure and heart rate were recorded continuously while patients were awake (four patients) or under general anesthesia (one patient). Recordings were made for 100 sec before stimulation, 100 sec during stimulation at one or two electrode locations within the PAG, and for 100 sec after stimulation. RESULTS:   Stimulation altered not only systolic and diastolic blood pressure but also heart rate. During stimulation, systolic blood pressure increased in three electrode positions by 7.2-10.2 mmHg, decreased in two electrode positions by 3.1-11.5 mmHg, and was unchanged in two electrode positions. Heart rate variability also changed during stimulation. Percentage systolic blood pressure change was positively correlated with change in high-frequency power (Pearson's r= 0.685, p= 0.09, N= 7), low-frequency : high-frequency power ratio (r= 0.667, p= 0.10, N= 7), and low-frequency power (r= 0.818, p= 0.02, N= 7), the latter of which was statistically significant. The percentages of the variance explained (r(2)) were 46.9, 44.5, and 66.9, respectively. CONCLUSIONS:   PAG stimulation modulates autonomic nervous system activity and thereby elicits changes in cardiovascular performance. Understanding of the mechanisms by which this therapy causes cardiovascular modulation will inform future innovation in this field with the aim of improving the efficacy and safety of patient treatment options.